Cerebral sinus venous thrombosis - Manorenj, Sandhya; Barla, Sudhaker (International Journal of Research in Medical Sciences, 2016)
Background: Intracranial Sino venous occlusive disease is an infrequent condition and accounts only 0.5-1% of all strokes. Objective of the study was to know the prevalence, pattern and risk factors involved in patients of cerebral sinus venous thrombosis (CSVT). Methods: Hospital databases were searched retrospectively and patients diagnosed with CSVT from December 2014 to February 2016 were identified. Data on clinical presentation, risk factor, cerebral sinus involved, hospital stay and outcome were analyzed. Results: Fifteen patients (3.4%) were identified as CSVT out of a total acute stroke case of 430. Mean age of patients was 31 years and 11 (73.3%) were males. The presenting symptoms included headache (n=14), altered sensorium (n=1) and seizures (n=5); signs included hemi paresis (n=4), papilledema (n=8) and bilateral VI nerve palsy (n=3). Majority had aseptic CSVT (n=14), and one patient had septic CSVT associated with tuberculous meningitis (TBM). Radiological findings included brain parenchyma involvement (n=8), subdural hematoma (SDH) (n=1), subarachnoid haemorrhage (SAH) (n=1) and normal brain parenchyma (n=5). Multiple cerebral sinuses were involved in seven patients. Most common site of CSVT was observed in sigmoid sinus. Risk factors included hyperhomocystenemia (n=3), protein S deficiency (n=8), protein C deficiency (n=6) and antithrombin III deficiency (n=3) as primary hypercoagulable state. ANA positive was observed in one patient and four had history of alcohol use. All fifteen patients received low molecular weight heparin (LMWH) for 1 week along with bridging oral anticoagulant. None of the patients required intrasinus thrombolysis and decompression surgery. Average hospital stay was 9 days. All had modified Rankin scale (MRS) ≤ 2 at 6 months follow up. Conclusions: Prevalence of CSVT is higher than that reported from Asian studies. Younger age and male predominance was observed. Protein S deficiency was the major risk factor for CSVT.